Static and dynamic voltage stability analysis - Pothula Uma Maheswara Rao (2008)
Voltage instability has been a great concern for quite a long time in electric power industry. A system enters a state of voltage instability due to increase in demand, a sudden large disturbance or a change in system condition that causes a progressive and uncontrollable decline in voltage. It is therefore interest to study both the dynamic and static aspects of voltage stability. Dynamic voltage stability can be divided into short-term and long-term based on the dynamics of the components that affect the voltage stability. In this study, dynamic models of various power system components (such as on load tap changing (OLTC) transformers, over excitation limiters (OXL), generators, induction motors, exponential loads etc.,) are successfully developed in MATLAB/ SIMULINK platform. The effect of induction motor load on short-term voltage stability of a simple power system is investigated using the network and motor P-V curves and the results found are then verified by observing the system states in time domain. The effects of the dynamics of slow-active devices, such as OLTC of a transformer, OXL of a generator, etc., on long-term voltage stability of a power system are also investigated in time domain. A computer program in MATLAB / SIMULINK environment is developed to investigate the long-term voltage instability and identify the reasons for dynamic voltage instability. Once the reason of voltage instability is identified, a remedial action using fixed capacitive reactive support is suggested to prevent the voltage instability. During a fault, the system voltage reduces drastically and that may cause to stall the induction motors. Stalling of induction motor can be prevented by clearing the fault as quickly as possible. A technique of determining the critical fault clearing time to prevent stalling of induction motor is also presented.